P-A6 Expression of HIV-1 matrix protein p17 and correlation with B cell lymphoma in HIV-1 transgenic mice. (March 2017) - Carroll, Virginia; Lafferty, Mark; Marchionni, Luigi; Bryant, Joseph; Gallo, Robert; Garzino-Demo, Alfredo
Abstract : HIV-1 infection is associated with increased risk for B cell lymphomas. Since HIV does not infect B cells, alternative mechanisms for transformation have been proposed. Current hypotheses on lymphomagenesis, based on immunosuppression, activation and/or inflammation, are generic and do not provide mechanistic, testable models. We hypothesized that HIV structural proteins may contribute to lymphomagenesis directly, as they can persist long-term in lymph nodes in the absence of viral replication. The HIV-1 transgenic mouse Tg26 carries a non-infectious HIV-1 provirus lacking part of the gag-pol region, thus constituting a model to study the effects of viral products in pathogenesis. About 15% of Tg26 mice spontaneously develop leukemia/lymphoma. Of the viral proteins examined, only expression of HIV-1 matrix protein p17 correlated with leukemia/lymphoma development and was highly expressed in bone marrow prior to disease. The tumor cells resembled pro-B cells, and were CD19+IgM-IgD-CD93+CD43+CD21−CD23-VpreB+CXCR4+. Consistent with the pro-B cell stage of B cell development, microarray analyses revealed enrichment of transcripts including Rag1 and Rag2 in lymphoma cells. We confirmed RAG1 expression in Tg26 tumors and hypothesized that HIV-1 matrix protein p17 may induce RAG1 in B cells directly. Stimulation of human activated B cells with p17 enhanced RAG1 expression in 3 of 7 donors, suggesting that intracellular signaling by p17 may lead to genomic instability and transformation. Thus, in addition to the reported angiogenic and lymphangiogenic activity of p17, extracellular matrix protein p17 has the potential to induce the enzymes responsible for DNA rearrangement and recombination in B cells.